Computer principles and design in Verilog HDL - Li, Yamin; Press, Tsinghua University (Wiley, 2015)
Uses Verilog HDL to illustrate computer architecture and microprocessor design, allowing readers to readily simulate and adjust the operation of each design, and thus build industrially relevant skills * Introduces the computer principles, computer design, and how to use Verilog HDL (Hardware Description Language) to implement the design * Provides the skills for designing processor/arithmetic/cpu chips, including the unique application of Verilog HDL material for CPU (central processing unit) implementation * Despite the many books on Verilog and computer architecture and microprocessor design, few, if any, use Verilog as a key tool in helping a student to understand these design techniques * A companion website includes color figures, Verilog HDL codes, extra test benches not found in the book, and PDFs of the figures and simulation waveforms for instructors